2015
DOI: 10.1063/1.4907995
|View full text |Cite
|
Sign up to set email alerts
|

Sanov and central limit theorems for output statistics of quantum Markov chains

Abstract: Horssen, Merlijn van and Guţă, Mădălin (2015) A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.For more information, please contact eprints@nottingham.ac.uk In this paper, we consider the statistics of repeated measurements on the ou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 49 publications
(88 reference statements)
1
39
0
Order By: Relevance
“…In the same spirit, we speculate that the above quantum equivalence results can contribute towards a better understanding of dynamical phase transitions on the level of quantum states. A possible application is the extension to continuous time of the Sanov Theorem for the empirical measure of multiple successive jumps, developed in [39]. In a different direction, the two ensembles set-up could be used to unify the existing system identification and asymptotic normality theory for discrete [40] and continuous [41] quantum Markov processes.…”
Section: Discussionmentioning
confidence: 99%
“…In the same spirit, we speculate that the above quantum equivalence results can contribute towards a better understanding of dynamical phase transitions on the level of quantum states. A possible application is the extension to continuous time of the Sanov Theorem for the empirical measure of multiple successive jumps, developed in [39]. In a different direction, the two ensembles set-up could be used to unify the existing system identification and asymptotic normality theory for discrete [40] and continuous [41] quantum Markov processes.…”
Section: Discussionmentioning
confidence: 99%
“…Various schemes for quantum parameter estimation based on repetitive or continuous measurements have been studied: see e.g. [17][18][19][20][21][22][23][24][25]. Among them, analogous setups were analyzed in [19,24], where the problem was formalized in terms of quantum Markov chains.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25]. Among them, analogous setups were analyzed in [19,24], where the problem was formalized in terms of quantum Markov chains. Specifically in [19] it has been shown that, under rather general assumptions, the statistics of the associated estimation problem converges asymptotically to a normal one, generalizing the similar results which were known to apply to purely classical settings [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…An important observation is that the bounds on fluctuations of a counting observable and its FPTs are controlled by the average dynamical activity, in analogy to the role played by the entropy production in the case of currents [1,13]. We hope these results will add to the growing body of work applying large deviation ideas and methods to the study of dynamics in driven systems [29][30][31][32][33][34][35][36][37][38][39][40][41], glasses [25,[42][43][44][45][46][47], protein folding and signaling networks [48][49][50][51], open quantum systems [52][53][54][55][56][57][58][59][60][61][62][63][64], and many other problems in nonequilibrium [65][66][67][68][69][70][71][72].…”
Section: Introductionmentioning
confidence: 99%